Dimensional structure of dairy farms in 2018 - Diana Cretu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
Romania's agriculture is of great diversity in terms of farm structure of production methods and technologies used. In this article, will be presented the dimensional structure of airy farms in 2018, highlighting issues such as the number of farms, the number of cattle, the number of farms and the number of cows depending on the type of farm, and the average size of cows' farms.
Keywords: Q11; Q13; 11; 330; dimensional structure; milking cows; weight